A review of tangle-veined flies (Nemestrinidae, Diptera) in Egypt - Arafa Elsayed El-Hashash (Pensoft Publishers, 2021)
The Egyptian fauna of the genus Nemestrinus Latreille, 1802 is revised. In 1967, Steyskal and El-Bialy listed 12 species from the region, but only six species are now recognized. The primary type specimens of the species N. aegyptiacus (Wiedemann, 1828), N. rufipes (Olivier, 1810), and N. lateralis Wiedemann, 1828 (N. lateralis being a synonym of N. rufipes) deposited in the Museum für Naturkunde, Berlin, Germany were examined. Two species (N. abdominalis Olivier, 1811 and N. fascifrons (Bigot, 1888) are placed as new synonyms of N. ater (Olivier, 1811), and N. ruficornis Macquart, 1840 is synonymized with N. rufipes (Olivier, 1811). Nemestrinus jullieni (Efflatoun, 1925) is confirmed as a synonym of N. aegyptiacus. Furthermore, three species (N. caucasicus Fischer, 1806, N. pallipes (Olivier, 1811), and N. persicus Lichtwardt, 1909) have been removed and are doubtful records from Egypt. A key to the species, lists of specimens examined, and Illustrations and distributions for each species are provided. The status of species of doubtful occurrence in Egypt is discussed.